Pawn Agricultural Land Pawn Agricultural Land (boroh) as Debt Guarantee in the Legal Perspective of Mu’amalah Fiqh in Sibio-bio village, East Angkola District, South Tapanuli - Ritonga, Sylvia Kurnia (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The practice of boro (pawning agricultural land) has been a long-standing tradition in Si bio-bio village which is detrimental to one of the parties, namely the pawnbroker, but it is still being carried out. Seeing this phenomenon requires an in-depth study of the legal aspects of muamalah fiqh. This article is a qualitative descriptive study to reveal the practice of pawning agricultural land (boroh) in the village of Sibio-bio which is then studied in Sharia law. Data collection techniques using observation techniques, interviews, and document studies. While the data analysis technique uses data triangulation, namely data collection, classification, and verification (drawing conclusions). The results of this study indicate that the pawning of agricultural land (boroh) was carried out by the people of Sibio-bio village due to the lack of a strong desire to save. The money obtained from pawning agricultural land is used for several needs such as building a house, children's education costs, child marriage costs, business capital, and buying vehicles. Regarding the legal status of pawning agricultural land (boroh) in the village of Sibio-bio, the clerics differed on the use of pawned goods (marhun), the Syafi'iyah explained that murtahin could use them, Malikiyah said murtahin could not control them, hanbilah clerics and Hanafiyah allowed it with Rahin's permission. The conclusion of this study is that pawning agricultural land is an act that is permitted, and the use of this land may be controlled by murtahin with permission from Rahin, and of course, it must be stated when the pawn agreement takes place